2017
DOI: 10.1002/etc.3945
|View full text |Cite
|
Sign up to set email alerts
|

Environmental behavior, potential phytotoxicity, and accumulation of copper oxide nanoparticles and arsenic in rice plants

Abstract: Copper oxide nanoparticles (CuO NPs) are widely used in many industries. The increasing release of CuO NPs from both intentional and unintentional sources into the environment may pose risks to rice plants, thereby reducing the quality or quantity of this staple grain in the human diet. Not only has arsenic (As) contamination decreased rice yield, but As accumulation in rice has also been a great human health concern for a few decades. New technologies have succeeded in removing As from water by nanomaterials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 121 publications
0
29
0
Order By: Relevance
“…Copper is seen as the third most important metal due to its daily use, and it is important for most living creatures [85]. Cu is an important micronutrient required by plants and should be administered at very low doses.…”
Section: Copper and Copper Oxide Nanoparticles (Cuo Nps)mentioning
confidence: 99%
“…Copper is seen as the third most important metal due to its daily use, and it is important for most living creatures [85]. Cu is an important micronutrient required by plants and should be administered at very low doses.…”
Section: Copper and Copper Oxide Nanoparticles (Cuo Nps)mentioning
confidence: 99%
“…The purity of CuO NPs was greater than 97%, and the pH of CuO NP suspensions (2000 mg/L) was 6.36 ± 0.02. Details of the TEM figure and the zeta potential of CuO NP suspensions have been published previously [21].…”
Section: Cuo Np Characterizationmentioning
confidence: 99%
“…As shown in Figure 3B, the SOD activity was significantly upregulated by 166% (p < 0.05) in the rice roots treated with 125 mg/L CuO NPs, but no changes were observed in the rice leaves. Based on previous studies, many factors have been suggested as potential mechanisms of CuO NPs causing phytotoxicity, e.g., DNA damage, metal ions released from NPs, ROS generation, and oxidative stress [21]. Among them, oxidative stress has attracted considerable attention [28,30].…”
Section: Antioxidant Enzyme Activity Of Rice Seedlingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded their work by fi nding that cellular toxicity of copper nanoparticles and increasing of reactive oxygen nanoparticles are responsible for the effect. Toxicity of copper oxide nanoparticles is also manifested on plants (165). In a complex experiment, Rajput and co-workers described the impact of copper oxide nanoparticles on spring barley (Hordeum sativum) as a representative staple food crop (166).…”
Section: Copper Nanoparticlesmentioning
confidence: 99%